2002
DOI: 10.1161/01.cir.0000038984.30279.89
|View full text |Cite
|
Sign up to set email alerts
|

Coated Stents for the Prevention of Restenosis: Part II

Abstract: T his is the second part of a 2-part article that reviews the literature on coated stents and their effects on in-stent restenosis after percutaneous coronary intervention (PCI). Part I of this review discussed the pathophysiology of in-stent restenosis, specific stent coatings, and animal studies investigating coated stents. Part II discusses nonrandomized studies and clinical trials in humans. Studies in humans have examined stents coated with biocompatible materials and drug-eluting stents. Complications an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
81
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(83 citation statements)
references
References 57 publications
1
81
0
1
Order By: Relevance
“…Recently, an increasing number of animal and human studies have shown significant reductions in intimal thickening associated with attenuated PI3K/Akt/mTOR/p70S6K signaling after rapamycin treatment. [21][22][23][24][25][26][27][28] Two-year follow-up studies in humans have shown persistent inhibition of in-stent restenosis with few, if any, adverse effects, which demonstrates the effectiveness and safety of rapamycin. 27,28 Our studies show the high proliferative capability, even under serum-deprived conditions, exhibited by both embryonic and neointimal SMCs is dependent on low PTEN activity resulting in constitutive Akt-dependent Figure 5.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Recently, an increasing number of animal and human studies have shown significant reductions in intimal thickening associated with attenuated PI3K/Akt/mTOR/p70S6K signaling after rapamycin treatment. [21][22][23][24][25][26][27][28] Two-year follow-up studies in humans have shown persistent inhibition of in-stent restenosis with few, if any, adverse effects, which demonstrates the effectiveness and safety of rapamycin. 27,28 Our studies show the high proliferative capability, even under serum-deprived conditions, exhibited by both embryonic and neointimal SMCs is dependent on low PTEN activity resulting in constitutive Akt-dependent Figure 5.…”
Section: Discussionmentioning
confidence: 95%
“…[21][22][23] Most approaches to limit the rate of restenosis, designed to target factors that stimulate growth of traditional adult-derived serum-dependent SMCs, 16,17,21 have been largely unsuccessful. Recently, an increasing number of animal and human studies have shown significant reductions in intimal thickening associated with attenuated PI3K/Akt/mTOR/p70S6K signaling after rapamycin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…56 Taken together, these considerations underscore the complexity of these model systems and suggest that preclinical testing of novel therapeutic targets in restenosis ultimately requires the use of species such as pigs, rabbits, or nonhuman primates before testing in human subjects. 57,58 …”
Section: Diabetes and Restenosis: Other Models And Distinct Interventmentioning
confidence: 99%
“…The polymer-regulated delivery of both paclitaxel and sirolimus at the site of arterial injury has been shown to reduce clinical and angiographic restenosis rates after stent implantation in de novo coronary lesions. [1][2][3][4][5][6][7] Specifically, in the pivotal TAXUS-IV trial, slow-release paclitaxel-elution from the TAXUS stent resulted in lower 9-month rates of target-lesion revascularization (TLR), target-vessel revascularization (TVR), and binary restenosis than bare-metal control stents. 7 Longer-term follow-up from this trial has not been reported, nor have clinical TLR rates been examined in subgroups known to affect restenosis.…”
mentioning
confidence: 99%